Human social buffer in goats and dogs - Anna Scandurra; Biagio D’Aniello; Maria Elena Pero; Claudia Pinelli; Alfredo Di Lucrezia; Raffaella Tudisco; Piera Iommelli; Vincenzo Mastellone; Pietro Lombardi (Animal Cognition)
Abstract The primary goal of this study was to explore the social buffering effect that humans offer to goats and dogs with limited exposure to human socialization, particularly in situations involving interactions with unfamiliar humans. A total of 13 dogs and 14 goats were selected for the study, all of which had limited prior socialization with humans. Each animal was placed in a testing room with unfamiliar humans for 15 min. Three experimenters aimed to establish a comfortable environment, encouraging social interaction by offering food to the animals and assessing the animals’ willingness to accept food and their response to being approached and petted. If both conditions were satisfied, the animals were classified as “social”. If one or none of the conditions were met, the animals were classified as “not social”. Cortisol levels were measured by collecting blood samples before and after the test. Non-parametric tests together with a GzLM showed that the effect of human social buffering in goats was different in comparison to dogs: goats exhibited higher cortisol levels after the test, while dogs did not show a significant change. Further analysis demonstrated that “social” goats had a lower likelihood of experiencing significant changes in cortisol levels than dogs. Thus, once human interactions are accepted, both species could benefit from social buffering. In summary, this study enhances our understanding of how dogs and goats respond to social interactions with humans in the social buffering effect.